ANALISIS ETOS KERJA KARYAWAN - AULIA, MAYA (Indragiri Research Center (ingreat), 2023)
This research aims to determine employee attitudes, employee willingness to carry out work and employee seriousness when working on the work ethic of employees at PD. BPR Gemilang Tembilahan Indragiri Hilir Regency. The research was conducted in Indragiri Hilir Regency at PD. BPR Gemilang Tembilahan. From the research results, there is an influence between employee attitudes, willingness to carry out work, employee seriousness of 84% which is influenced by work ethic. The remaining 16% is influenced by other variables not examined in this research. Partially test that Employee Attitude (X1) partially influences the work ethic of employees at PD. BPR Gemilang Tembilahan. Willingness to carry out work (X2) partially influences the work ethic of employees at PD. BPR Gemilang Tembilahan. The seriousness of employees when working (X3) partially influences the work ethic of employees at PD. BPR Gemilang Tembilahan. Simultaneous tests show that employee attitudes, willingness to carry out work, and seriousness of employees when working together influence the work ethic of employees at PD. BPR Gemilang Tembilahan.